Study on the factors affecting the competitiveness of biopharmaceutical industry cluster: Evidence from Guangdong and Zhejiang of China - Qiu Zhang; Mandong Huang; Xiaoxin Huang; Lu Gan; Yiling Li; Huiying Huang (Journal of Holistic Integrative Pharmacy)
Objective: This study aims to analyze factors affecting the competitiveness of China's biopharmaceutical industry cluster, offering insights for policymakers and stakeholders, while providing Chinese experience and theoretical support for sustainable development of global biopharmaceutical industry clusters. Methods: Based on relevant data from Guangdong and Zhejiang Provinces in China, the entropy value method was used to evaluate the comprehensive competitiveness of biopharmaceutical industry clusters in Guangdong and Zhejiang provinces respectively, and the principal component regression method was applied to respectively examine factors affecting the competitiveness of biopharmaceutical industry clusters in Guangdong and Zhejiang provinces. Results: The competitiveness study showed that the comprehensive competitiveness scores of biopharmaceutical industry clusters in Guangdong and Zhejiang both show an upward trend from 2010 to 2020. From 2010 to 2020, the average value of Zhejiang's competitiveness was 0.53 and Guangdong's was 0.41. The influencing factor study showed that the top five factors affecting the competitiveness of biopharmaceutical industry clusters in Guangdong and Zhejiang were the same, namely, the ratio of general public service expenditure to regional GDP, ratio of regional road freight turnover to regional road mileage, proportion of R&D expenditure to total industrial output, ratio of total healthcare expenditure to provincial consumption, and product sales rate. Conclusion: The results suggested that core factors affecting the competitiveness of China's biopharmaceutical industry cluster center on four aspects: infrastructure, innovation resources, enterprise performance, and market environment. Therefore, the primary strategy is to strengthen infrastructure construction and investment in innovation resources, while balancing enterprise performance with market environment optimization. This study pioneered the research on factors influencing the competitiveness of China's biopharmaceutical industry cluster, providing a new perspective and reference framework for subsequent research in this field.